Drivers of migration and determinants of wellbeing among internal youth migrants in Ethiopia: Towns along Addis Ababa –Adama route in focus - Habtamu Kebu; Oumer Berisso; Messay Mulugeta (Heliyon, 2023)
The present study surveyed drivers of rural youth influx to urban areas and examined correlates of wellbeing among youth migrants domiciled in towns along important economic corridor of Ethiopia. In total, 694 (M = 418, F = 276) youth migrants aged 15–30 years and identified through multistage and purposive sampling techniques filled in a self-report questionnaire consisting of items probe profile and rating scales intended to uncover circumstantial and intentional activities of respondents. Descriptive statistics, Pearson's product momentum correlation, and multiple regression analysis were utilized to examine the data. The results show that most migrants are single and short distance migrants with secondary education and above. Both “push” and “pull” factors are found to be key factors driving youth to urban areas. The persistent challenges these youth migrants faced at destination areas include high living cost, housing problems and joblessness ˗˗ the existing Ethiopian urban area scenario, which is likely to be exacerbated by their very presence. Besides, the analysis of the relationship of circumstantial factors and intentional activities with indicators of wellbeing revealed a strong association of proactive coping behaviour with both indicators of participants' wellbeing (i.e., income and perceived subjective wellbeing). Sex and educational level are related with income, and perceived support from other is associated with perceived subjective wellbeing. The findings of the study provide additional evidence on drivers of youth migrants in developing countries and highlight some determinant factors that account for youth migrants' wellbeing. Implications of the study are discussed.